Explorative study of apple juice fluorescence in relation to antioxidant properties. (1st November 2016) - Włodarska, Katarzyna; Pawlak-Lemańska, Katarzyna; Khmelinskii, Igor; Sikorska, Ewa
Highlights: Fluorescence characteristics of differently processed apple juices. Three groups of fluorophores revealed by parallel factor analysis. Relationship between fluorescence and total phenolic content, and antioxidant capacity. Usefulness of fluorescence for screening the antioxidant properties of apple juices. Abstract: Total fluorescence spectra (excitation-emission matrices, EEM) were recorded for a series of commercial apple juices, including clear and cloudy juices produced from concentrate, cloudy juices that were not from concentrate, and freshly squeezed juices. An exploratory study of the spectra with parallel factor analysis (PARAFAC) revealed three groups of fluorophores with different emission properties, and these properties were characterized by excitation/emission maxima at 270/315 nm, (310, 370)/455 nm, and 430/(550, 680) nm, respectively. A regression analysis of the total fluorescence spectra arranged into three-way arrays using N -way partial least squares regression methods ( N PLS1 and N PLS2) and an analysis of the unfolded spectra by partial least squares methods (PLS1 and PLS2) revealed quantitative relations between the fluorescence and antioxidant properties of juices. The best models for the total phenolic contents and total antioxidant capacities were obtained by applying the N PLS1 method to the EEM. The model parameters were as follows: R 2 CV  = 0.802, RPD = 2.3 for the total phenolic content and R 2 CV  = 0.808 and RPD = 2.3 for the total antioxidant capacity. These results show the potential use of fluorescence spectroscopy for screening apple juices for their antioxidant properties.